Prevalence and Anthropometric Factors Associated with Flat Foot Among University Students - Yudiansyah; Ika Guslanda Bustam (Universitas Negeri Semarang, 2026)
Flat foot (pes planus) is a deformity characterized by collapse of the medial longitudinal arch, which may lead to postural disturbances and functional limitations. Despite its clinical relevance, flat foot often receives little attention until musculoskeletal symptoms become pronounced. Epidemiological data on its prevalence and anthropometric determinants among university students, particularly in Southeast Asia, remain limited. This study aimed to determine the prevalence of flat foot and its association with gender, age, body weight, height, and body mass index (BMI) among university students as a basis for early prevention strategies. A quantitative descriptive, cross-sectional study was conducted involving 107 university students (21 males and 86 females). Foot arch structure was assessed using the footprint test, and data were analyzed using descriptive and inferential statistics. Flat foot prevalence was higher in females (67.29%) than males (14.95%) and was most common in respondents aged 21–23 years (64.49%). Higher prevalence was observed among students with body weight ≥60 kg (33.64%), height ≥166 cm (18.69%), and elevated BMI. Anthropometric factors, particularly gender, body weight, height, and BMI, are significantly associated with flat foot prevalence among university students.